2004
DOI: 10.1103/physrevlett.93.038101
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Developmental Canalization in Networks of Competing Boolean Nodes

Abstract: Developmental canalization, which leads to a reduction in the variation of phenotype expression relative to the complexity of the genome, has long been thought to be an important property of evolving biological systems. We demonstrate that a highly canalized state develops in the process of self-organization recently discovered in N-K Boolean networks that evolve based on a competition between the nodes. The model provides a simplified description of the evolution of genetic regulatory networks in developmenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 28 publications
3
38
0
Order By: Relevance
“…In a simulation study of the evolution properties of the different Boolean functions, Bassler et al [29] observed that functions with k = 3 inputs fell into 14 distinct classes. In their study all of the functions that were members of the same class evolved, on average, with equal probability.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a simulation study of the evolution properties of the different Boolean functions, Bassler et al [29] observed that functions with k = 3 inputs fell into 14 distinct classes. In their study all of the functions that were members of the same class evolved, on average, with equal probability.…”
Section: Resultsmentioning
confidence: 99%
“…In mathematical terms, the classes that were identified empirically in Ref. [29] are group orbits. We illustrate the mapping for the sixteen k = 2 functions in figure 2, where the rotational plus parity symmetries of the functions belonging to each of the four classes are obvious.…”
Section: Resultsmentioning
confidence: 99%
“…These 14 Zyklenzeiger classes are labeled from A to J, according to the canalization properties of the functions in the class. Additionally, those functions labeled C, F , and H, form multiple classes, designated with subscripts, to distinguish those with the same canalization properties but different internal homogeneity and parity symmetry [51]. The 10 function classes of critical network dynamics result from combining the Zyklenzeiger classes designated with subscripts.…”
Section: Symmetry In Other Dynamicsmentioning
confidence: 99%
“…The mutations affect the connections and the update functions of the nodes. Compared to the simulations in [8,9,10,11,12,13,14,15,16], fitness can be changed by more types of mutations in our model. We let the networks evolve freely under a biologically motivated fitness criterion without imposing any "target properties" to find network topologies that are evolutionary robust.…”
Section: Introductionmentioning
confidence: 99%
“…The network evolves to a stationary state "at the edge of chaos". Further studies of the model [13] showed that the evolved networks are highly canalized. Other models that evolve to a critical state are studied in [14,15,16].…”
Section: Introductionmentioning
confidence: 99%